«Workers, do not vote!». CNT and Spanish Popular Front in the 1936 general elections | «Obreros, no votéis». La CNT y el Frente Popular en las elecciones de 1936 - Roberto Villa García (Pasado y Memoria, 2014)
This article aims to explain the position of CNT and FAI in the general elections of 1936. It analyzes how propagandists of both organizations understood the instructions, approved in their plenary meetings, during the election campaign. A comparison with anarcho-syndical propaganda of November 1933, as well as an analysis of the different points of view that CNT and the leftist coalition called Popular Front had about amnesty and fascist danger, challenge the idea that they shared similar interests in 1936 and that laxity in the anarchist position against politics and elections took place therein. | Este artículo pretende aclarar la postura de la CNT y la FAI ante las elecciones generales de 1936. Se analiza cómo tradujeron los propagandistas de ambas organizaciones las ponencias electorales aprobadas en sus Plenos durante la campaña electoral. La comparación con la propaganda anarcosindicalista de noviembre de 1933 y el análisis de las concepciones dispares que la CNT y las izquierdas coaligadas en el Frente Popular mantenían sobre la amnistía y el peligro fascista, cuestionan que en 1936 se produjera una convergencia de intereses entre ambas y, por tanto, un relajamiento en las posiciones apolíticas y antielectorales de aquélla.